Reconstituting the “Un-Person”: The Khmer Krom and the Khmer Rouge Tribunal - MOHAN, Mahdev (Institutional Knowledge at Singapore Management University, 2010)
Despite the grand promise of victim participation at the ongoing trials of Extraordinary Chambers in the Courts of Cambodia (“ECCC”), this article notes the plight of an undeserved ethnic community, the members of which have become forgotten victims of genocide. The Article argues that if the ECCC’s trials are to have any resonance for the Khmer Krom, its affiliates and victims’ lawyers should avoid “othering” Khmer Krom victims of genocide, and instead adopt ethnographic approaches to lawyering that seek to ascertain communal desires for vindication.